The genusNotomastus(Polychaeta: Capitellidae) in the Gulf of California, Mexico, with the description of three new species - García Garza, María Elena; De León González, Jesús Ángel (Biological Society of Washington, 2015)
Several surveys of polychaetes from intertidal and deep water habitats in the Gulf of California, Mexico have yielded nine species of Notomastus (Annelida: Capitellidae), three being undescribed species: Notomastus landini n. sp., Notomastus lobulatus n. sp. and Notomastus fauchaldi n. sp. Standardized descriptions are provided for all species including details of epithelial texture, position of lateral organs, shape of noto-and neuropodial lobes, the shape of hooded hooks and the methyl green staining pattern. In addition, a key to all Notomastus species included in the Gulf of California is provided.